2008
DOI: 10.4049/jimmunol.181.2.1556
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Genes in Addition to Tlr7 in the Yaa Translocation Linked with Acceleration of Systemic Lupus Erythematosus

Abstract: The accelerated development of systemic lupus erythematosus (SLE) in male BXSB mice is associated with the genetic abnormality in its Y chromosome, designated Yaa (Y-linked autoimmune acceleration). Recently, the Yaa mutation was identified to be a translocation from the telomeric end of the X chromosome (containing the gene encoding TLR7) onto the Y chromosome. In the present study, we determined whether the Tlr7 gene duplication is indeed responsible for the Yaa-mediated acceleration of SLE. Analysis of C57B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
101
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 37 publications
13
101
0
Order By: Relevance
“…This observation is consistent with our recent results obtained in lupus models in which disruption of the tlr7 gene was responsible for a decreased frequency of splenic B cells [27]. Although MOG-induced EAE has long been considered an exclusively CD4 + T-cell-mediated disease, the role of B cells in this pathology is now well established.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This observation is consistent with our recent results obtained in lupus models in which disruption of the tlr7 gene was responsible for a decreased frequency of splenic B cells [27]. Although MOG-induced EAE has long been considered an exclusively CD4 + T-cell-mediated disease, the role of B cells in this pathology is now well established.…”
Section: Discussionsupporting
confidence: 82%
“…3D evidence for a reduction of CNS inflammation in TLR7-deficient mice. Collectively, our results indicated that TLR7 plays an active and deleterious role in sustaining autoimmune responses in MOGinduced EAE, which is in line with previous observations in murine lupus [4,15,[27][28][29].Inhibition of B-cell activation in TLR7 −/− mice is associated with decreased antibody responsesAs mentioned previously, self-derived nucleotides may reach B cell or pDC endosomes (containing TLR7) in autoimmune situations through the action of nucleotide-binding proteins such as autoantibodies [18]. Consequently, TLR7 is involved in the activation of B cells and pDCs by RNA-associated autoantigens through BCR and/or FcγR IC ligation and endocytosis followed by RNA autoantigen transfer from disrupted IC to TLR7.…”
supporting
confidence: 81%
“…Similarly, antigenic cargo containing nucleic acids was found to promote B-cell proliferation in a TLR9-or TLR7-dependent manner, with this effect enhanced by type I IFN signaling (9,12,13). The contribution of nucleic acid-sensing TLRs to systemic autoimmunity was further corroborated by studies in lupus-predisposed mice lacking or overexpressing TLR7 and/or TLR9 (14)(15)(16)(17)(18)(19)(20), and in Unc93b1 (3d) mutant mice in which signaling by endosomal TLRs is extinguished (21).…”
supporting
confidence: 53%
“…18 Genetic overexpression of X-linked genes, as observed in mice carrying the Y-linked autoimmune accelerator lupus susceptibility locus including TLR7, has also been strongly associated with lupus disease development. 19,20,21,22,23 Of note, topical treatment of wild-type mice with TLR7 agonists leads to lupus-like autoimmunity in several strains of mice. 10 In addition, previous studies have focused on the effect of B cell-intrinsic TLR7 signaling on immune activation, autoantibody repertoire, systemic inflammation, 18,24 and the development of GCs.…”
Section: Introductionmentioning
confidence: 99%